(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
Niosomes, vesicular systems derived from non-ionic surfactants, have been identified as highly promising carriers for drug delivery owing to their biocompatibility, stability, and capacity to encapsulate both hydrophilic and lipophilic pharmacological agents. These self-assembled bilayer vesicles, which consist of non-ionic surfactants and cholesterol, present several advantages such as extended circulation duration, targeted therapeutic delivery, and controlled release mechanisms. In comparison to liposomes, niosomes demonstrate superior stability and a diminished vulnerability to oxidative degradation and hydrolytic processes. A variety of formulation techniques, including thin-film hydration, sonication, and reverse-phase evaporation, facilitate the optimization of niosomal formulations for a range of therapeutic applications. Niosomes have been rigorously investigated for their potential applications in transdermal delivery, ocular therapy, pulmonary treatment, oncological therapy, as well as in vaccine and gene delivery systems. Notwithstanding their numerous advantages, obstacles such as vesicle aggregation, drug leakage, and constraints in large-scale manufacturing necessitate further investigation to enhance formulations’ stability and commercial feasibility. This review aims to furnish a thorough overview of the composition, preparation methodologies, characterization techniques, and pharmaceutical applications of niosomes, underscoring their promise as an efficacious system for drug delivery within contemporary therapeutics.